Effects of Process-Induced Voids on the Properties of Fibre Reinforced Composites - Dong, Jonathan (Zhongguo Kexueyuan Jinshu Yanjiusuo, 2015)
It is well known that voids have detrimental effects on the performance of composites. This study aims to provide a practical method for predicting the effects of process induced voids on the properties of composites. Representative volume elements (RVE) for carbon fibre/epoxy composites of various fibre volume fractions and void contents are created, and the moduli and strengths are derived by finite element analysis (FEA). Regression models are fitted to the FEA data for predicting composite properties including tensile, compressive and shear. The strengths of composite laminates including tensile strength and interlaminar shear strength (ILSS) are calculated with the aid of the developed models. The model predictions are compared with various experimental data and good agreement is found. The outcome from this study provides a useful optimisation and robust design tool for realising affordable composite products when process induced voids are taken into account.